Implementasi Ajaran Smaranam dalam meningkatkan Sradha dan Bhakti Siswa Hindu - Andari, Ida Ayu Made Yuni (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This research is aimed at analyzing and finding how to apply one of the true bhakti teachings, Smaranam in improving learners' sradha and bhakti. This method of research uses descriptive qualitative methods, in which the characteristic of this study is digging into a phenomenon in depth. Smaranam is one part of Nawa Widha Bhakti’s teaching: mentioning repeatedly the holy name of God (japam). This refers to the current phenomenon in which technological development makes learners addicted to it and forget their activities, such as performing prayers. Therefore, there needs to be implementation of religious teachings that can cultivate and improve the students'sradha and bhakti. With the implementation of true bhakti teachings, one of them Smaranam at State High School 4 Mataram can grow and improve the sradha and bhakti of Hindu students, which can be seen from the student’s awareness of duties and obligations such as praying well. It can be concluded that the implementation of Smaranam teachings is effective in efforts to improve the students' sradha and bhakti.